MEKANISME GOOD CORPORATE GOVERNANCE, KUALITAS AUDIT, UKURAN PERUSAHAAN DAN KORELASINYA TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Gilang Darmawang, SE., M.Ak.; Suratno Suratno; Muhammad Yusuf (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
This study aims to identify, analyze, demonstrate and test the mechanisms of good corporate governance, audit quality, the size of the company and its correlation on the value of the company with earnings management as an intervening variable in manufacturing companies and consumer goods industry sectors listed on the Indonesia Stock Exchange period 2011-2015. This study uses secondary data to see and obtain data from the Indonesia Stock Exchange. The research method in this research is by using Path Analysis with two substructures. The results show that good corporate governance partially no effect on earnings management, audit quality has influence but not significant to earnings management, the size of the company has a significant influence on earnings management, good corporate governance with significant influence on the value of the company, audit quality has an impact and significantly to the value of the company, company size has no significant effect on firm value. The tests are based on a confidence level of 95%, and an error rate of 5%.